Hubungan Antara Pola Adaptasi Dampak Perubahan Iklim Dan Pendapatan Nelayan Di Kota Kupang, Nusa Tenggara Timur - Dulce Aryani Batukh (Environmental Research Center (PPLH) of Udayana University, 2023)
Kupang City is one of the areas that has become a marketing center for marine fish in East Nusa Tenggara Province. Climate change has a negative impact on coastal areas, especially the life activities of fishing communities. The negative impacts of climate change include extreme weather, changes in rainfall patterns and large waves. sustainable impact on Fishermen is abnormal fishing activity this has an impact on income. Based on the correlation analysis, the wind speed variabel (X4) is correlated to Y with a significance value of 0.001 < 0.05. Meanwhile, the variabels of temperature (X1), rainfall (X2), and wave height (X3) have a weak relationship to the income variabel Y. SWOT analysis on adaptation patterns carried out by fishermen SO: Optimization of fishing when the selling price of fish rises and Combination of several types of work / development of income sources. Use of a variety of fishing tools and techniques. WO: Situational individual strategy. WT: Joint capital development, Establishing strong and long-lasting relationships with other parties in obtaining capital and marketing the catch. ST: Mobilizing household members in economic activities (role of wife and children).